Inhibitory effects of three opioid receptor agonists on synaptic transmission - Yuan Xiao-Ru (Acta Pharmacologica Sinica, 2016)
"AIM: To compare the inhibitory effects of 3 opioid receptor agonists, (D-Ala2, NMe-Phe4, Gly-ol)-enkephalin (DAGO), (D-Pen2,5)-enkephalin (D-PEN), and trans-(+/-)-3, 4-dichloro-N-methyl-N-[2-(1-pyrrolidinyl) cyclohexyl]-benzeneacetamide methanesulfonate (U-50488H) in different concentrations on synaptic transmission. METHODS: The excitatory postsynaptic potentials (EPSP) in slice preparation of nucleus accumbens of rats were recorded using electric stimulation of the olfactory tubercle area and intracellular micropipettes filled with potassium acetate (3 mol.L-1). RESULTS: Superfusion of DAGO, D-PEN, and U-50488H (1 mumol.L-1) reduced the amplitude of EPSP and the inhibitory effect on EPSP were reversed by superfusing naloxone (Nal, 1 mumol.L-1), in which the DAGO-induced reduction of synaptic transmission was the most effective. The depolarizing responses to microiontophoretic injection of glutamate were reduced by superfusing DAGO in 19 neurons of slice preparation of nucleus accumbens. CONCLUSION: The inhibitory effects of DAGO, D-PEN, and U-50488H on EPSP were in a concentration-dependent manner, and the mechanism of opioid agonists (at least DAGO) reducing EPSP was related to a decrease of postsynaptic transmission mediated by glutamate. "